Peculiarities of administration of medications to patients with circulatory system diseases within the framework of the federal program of preferential provision of medicines - I. K. Petrukhina; R. I. Yagudina; N. V. Veyner; T. K. Ryazanova; E. P. Gladunova; V. A. Kurkin; P. R. Blinkova; E. N. Zaitseva (IRBIS LLC, 2021)
Objective: to analyse of medicines prescriptions for federal beneficiaries with circulatory system diseases and to identify the main trends in the implementation of the federal program for the provision of necessary medicines in the Samara Region in 2014-2017.Material and methods. The authors reviewed the nomenclature of medicines used to treat circulatory system diseases (CSDs) and distributed to the population of the Samara Region as part of the federal program for the provision of necessary medicines for the period from 2014 to 2017. The methods of comparative, retrospective, logical, graphical and content analysis, the method of data grouping according to Anatomical Therapeutic Chemical classification and methods of descriptive statistics were used.Results. In 2014-2017 the share of financial costs for the purchase of medicines in the total budget of the federal program for the provision of necessary medicines in the Samara Region did not exceed 6%. Still, in physical terms (in terms of the number of packages) the share of medicines of this pharmacotherapeutic group in the federal program for the provision of necessary medicines averaged about 25%. Nomenclature of medicines of the analyzed group prescribed to federal beneficiaries in 2014-2017 ranged from 90 to 107 nomenclature items. The number of international nonproprietary names (INN) decreased from 51 in 2014 to 36 in 2017. During the period under review, there was a decrease in the acquisition cost of medicines for the treatment of circulatory system diseases and the weighted average cost of one package (by 63% and 53%, respectively).Conclusion. Perindopril-containing medicines occupied the maximum consumption volumes in monetary terms. There was a decrease in the average cost of one package in 2017, which may be associated with the replacement of original medicines with generics and a concomitant reduction in the number of INN within the subgroup.